Carbazole modified ruthenium complex and preparation method and application of electro-polymerization film based on ruthenium complex
The ruthenium complex modified by carbazole is grafted with metal organic polymer film on the surface of the ITO electrode, which solves the problems of poor adhesion and low conductivity of covalent self-assembly materials on the surface of traditional electrodes, and achieves efficient electron transfer and photoelectric conversion efficiency.
Patent Information
- Application Number
- CN202510024506.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-18
AI Technical Summary
The existing metal organic polymer electrodes have problems of poor adhesion and low conductivity in electrochemical applications, which limit their applications in energy conversion and storage, electrocatalysis, electrochemical sensors, etc.
The ruthenium complex modified with carbazole was grafted on the surface of the ITO electrode by constant potential electropolymerization technology, and the adhesion and conductivity of the film were enhanced by covalent bonds.
It realizes efficient electron transfer rate constant, photocurrent density and photoelectric conversion efficiency, which significantly improves the stability and application prospects of the film.
Smart Images

Figure CN119841871A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photoelectric sensors, and in particular to a carbazole-modified ruthenium complex and a preparation method and application of an electropolymerized film based on the ruthenium complex. Background Art
[0002] Metal organic polymers have attracted extensive attention in basic science and practical applications due to their rich redox properties, high stability, easy modification, and diverse structures. Among them, metal complex modified electrodes have been widely used in energy conversion and storage, electrocatalysis, electrochemical sensors, and biosensors. Conjugated polymer materials have attracted extensive attention due to their high visible light absorptivity, intrinsic high carrier mobility, and excellent thin film processing properties. However, due to irreversible redox processes, the coexistence of electrochemical instability and the poor charge capture properties of these pure organic polymers limit their practical applications. Ru(II)-bipyridyl complexes have been widely used as photosensitizers in solar cells and light-driven catalysis (such as photolysis). In particular, Ru(II) complexes modified with strong electron-withdrawing / donating ligands prolong the excited state lifetime and enhance its absorption of visible light, which makes them effective photosensitizer dyes. Electrochemically directly driven coordination polymer electrodes avoid the multi-step synthesis route of introducing anchoring groups and spacer groups into the molecular skeleton and the complex purification steps, but this method has the disadvantages of poor adhesion of the film to the electrode surface and relatively low electron transfer rate.
[0003] At present, there is no report in the literature on the electropolymerized film of the carbazole-modified ruthenium complex studied in the present invention. Summary of the invention
[0004] The purpose of the present invention is to provide a carbazole-modified ruthenium complex and a preparation method and application of an electropolymer film based on the ruthenium complex in view of the above-mentioned problems. The present invention provides a new and efficient technology for grafting a metal organic polymer film on the electrode surface by covalent bonds. The metal organic polymer film is grafted on the electrode surface by covalent bonds, which can change the shortcomings of poor adhesion and relatively low conductivity of covalent self-assembled materials on the surface of traditional electrodes.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] The present invention first provides a carbazole-modified ruthenium complex, the structural formula of which is shown in formula (I):
[0007]
[0008] The chemical formula is [Ru(bpy)2HL](ClO4)2, where bpy represents bipyridine and HL is a ligand. The chemical name of the ligand is N-(4-(9H-carbazole-9-yl)phenyl)-4-(9H-carbazole-9-yl)-N-(4-(3a,11b-dihydro-1H-imidazo[4,5-f][1,10]phenanthroline-2-yl)phenyl)aniline, and the structural formula is shown in formula (II):
[0009]
[0010] The present invention also provides a method for preparing a carbazole-modified ruthenium complex, comprising the following steps:
[0011] (1) Synthesis of ligand HL: 1,10-phenanthroline-5,6-dione, 4-(bis(4-(9H-carbazole-9-yl)phenyl)amino)benzaldehyde, ammonium acetate and glacial acetic acid are placed in a reaction vessel and reacted at 120±1°C. After the reaction is completed, the reaction solution is quickly poured into ice water, and the pH of the solution is adjusted to neutral with ammonia water. The solution is allowed to stand and filtered to obtain a crude product. The crude product is recrystallized with a mixed solvent of DMF / water, filtered, the precipitate is collected, and the filter cake is washed with anhydrous ethanol. The product is vacuum dried to obtain a yellow-brown powdery solid, which is the ligand HL.
[0012] (2) Synthesis of the complex [Ru(bpy)2HL](ClO4)2: The ligand HL and Ru(bpy)2Cl2 were dispersed in anhydrous ethanol and refluxed in the dark under nitrogen protection. After cooling, most of the solvent was removed by rotary evaporation. The remaining reaction solution was separated by column chromatography and the main orange portion was collected. After most of the acetonitrile was removed by rotary evaporation, sodium perchlorate solution was added thereto. After stirring, the precipitate was collected by filtration. The precipitate was dissolved with a small amount of acetonitrile, and recrystallized by diffusion with ether / acetonitrile. After vacuum drying, an orange-red powder was obtained.
[0013] In the above preparation method, preferably, in step (1), the molar ratio of 1,10-phenanthroline-5,6-dione, 4-(bis(4-(9H-carbazole-9-yl)phenyl)amino)benzaldehyde and ammonium acetate is 1:1:20.
[0014] In the above preparation method, preferably, in step (2), the molar ratio of the ligand HL and Ru(bpy)2Cl2 is 1:1.
[0015] In the above preparation method, preferably, in step (1), the reaction time is 2 hours.
[0016] The present invention also provides an electropolymerized film based on a ruthenium complex, which is obtained by modifying the ruthenium complex onto an ITO electrode using a constant potential electropolymerization method. Specifically, the steps include: first, the ITO glass electrode is cleaned, then, the ruthenium complex is dissolved in dichloromethane, and tetrabutylammonium hexafluorophosphate is used as a supporting electrolyte; ITO is used as a working electrode, a platinum electrode is used as a counter electrode, and an Ag / AgNO3 electrode is used as a reference electrode, nitrogen is introduced into the solution, and a constant potential method is used with a 40s time gradient to assemble ruthenium complex electropolymerized films of different thicknesses.
[0017] In the above method for preparing the electropolymerized film, preferably, the concentration of the ruthenium complex in dichloromethane is 1 mM.
[0018] The present invention also protects the application of the electropolymer film in energy conversion and oxygen sensor.
[0019] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0020] 1. The present invention provides a new and efficient technology for grafting metal organic polymer films on the surface of an electrode using covalent bonds. The technology for grafting metal organic polymer films on the surface of an electrode using covalent bonds can change the shortcomings of poor adhesion and relatively low conductivity of covalent self-assembled materials on the surface of traditional electrodes.
[0021] 2. The present invention adopts the method of constant potential electropolymerization to modify the carbazole-modified ruthenium (II) complex onto the ITO electrode, and measures the electron transfer rate constant, photocurrent size, and monochromatic light conversion efficiency of the thin film electrode. The results show that the electron transfer rate constant of the film is relatively large, reaching 6.26s -1 When the applied bias voltage is -0.4V, the photocurrent of the film is the largest, at 100mW / cm 2 Under white light irradiation, the film polymerized at constant potential for 80 s showed a maximum photocurrent density of 5.74 μA / cm in a 0.1 M Na2SO4 aqueous solution without air. 2 After the film was placed at room temperature for 3 months, its photocurrent only decayed by 11.7%, indicating that the film had good stability. When oxygen was introduced into the electrolyte solution, the photocurrent density increased to 14.07 μA / cm 2 The photoelectric conversion efficiency is 0.61%, indicating that the electropolymer film has application prospects in energy conversion and oxygen sensors. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1The cyclic voltammetry curve of the polymerized film obtained by constant potential electropolymerization of carbazole-modified ruthenium (II) complex for 80s changes with the scan rate of 0.05-1V / s. The inset shows the relationship between the oxidation (reduction) peak current and the scan rate.
[0023] Figure 2 The cyclic voltammetry curve of the polymerized film obtained by constant potential electropolymerization of carbazole-modified ruthenium (II) complex for 80s changes with the scanning rate of 1-10V / s. The inset is the linear fitting diagram of the plot of △Ep against logv.
[0024] Figure 3 It curves of carbazole-modified ruthenium (II) complex film electrodes at different bias voltages (the ah bias voltages are -0.4V to +0.3V, and the bias voltage change interval is 0.1V);
[0025] Figure 4 The it curves of the carbazole-modified ruthenium (II) complex thin film electrode at a bias voltage of -0.4 V for the newly prepared film (a) and the film after being stored at room temperature for 3 months (b);
[0026] Figure 5 The graph is a graph showing the IPCE value of the carbazole-modified ruthenium (II) complex film electrode as a function of the wavelength of monochromatic light;
[0027] Figure 6 The photocurrent of the carbazole-modified ruthenium (II) complex thin film electrode under the conditions of -0.4V bias, air balance, N2 flow, and O2 flow. DETAILED DESCRIPTION
[0028] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. In the embodiments of the present invention, the raw material 4-(bis(4-(9H-carbazole-9-yl)phenyl)amino)benzaldehyde is synthesized by the method in the reference (Self-host homoleptic green iridium dendrimers based on diphenylaminedendrons for highly efficient single-layer PhOLEDs, Wenwen Tian etc. Journal of Materials Chemistry C, Published on 11 November 2013), and other raw materials are purchased from commercial channels.
[0029] Example 1 Preparation of ligand HL
[0030] The synthetic route of the ligand N-(4-(9H-carbazole-9-yl)phenyl)-4-(9H-carbazole-9-yl)-N-(4-(3a,11b-dihydro-1H-imidazo[4,5-f][1,10]phenanthroline-2-yl)phenyl)aniline (HL) is as follows:
[0031]
[0032] The synthesis method is as follows: 1,10-phenanthroline-5,6-dione (210 mg, 1.0 mmol), 4-(bis(4-(9H-carbazole-9-yl)phenyl)amino)benzaldehyde (603 mg, 1.0 mmol), ammonium acetate (1.54 g, 20 mmol), and glacial acetic acid (20 mL) are placed in a flask, reacted at 120±1°C for 2 hours, and after the reaction is completed, the reaction solution is quickly poured into 150 mL of ice water, and the pH of the solution is adjusted to neutral with ammonia water, allowed to stand, and filtered to obtain a crude product. The crude product is recrystallized with a mixed solvent of DMF / water (V / V=4 / 1), filtered, the precipitate is collected, and the filter cake is washed with anhydrous ethanol. Vacuum drying is performed to obtain 0.48 g of a yellow-brown powdery solid with a yield of 60%.
[0033] 1 H-NMR(δ / ppm,500MHz,DMSO-d6):8.27(d,J=5Hz,5H),7.88(d,J=7.5Hz,2H),7.7 2(d,J=7.0Hz,3H),7.58(d,J=8.0Hz,3H),7.51-7.46(m,14H),7.33-7.30(m,7H).
[0034] Example 2 Preparation of Complex [Ru(bpy)2HL](ClO4)2
[0035] The synthetic route of the complex [Ru(bpy)2HL](ClO4)2 is as follows:
[0036]
[0037] The synthesis method is as follows: HL (159 mg, 0.2 mmol), Ru (bpy) 2 Cl 2 (104 mg, 0.2 mmol) and 32 mL of anhydrous ethanol are added to a 50 mL flask, the mixed solution is uniformly dispersed by ultrasound, and then refluxed in the dark for 24 h under nitrogen protection. After the reaction is completed, it is cooled to room temperature, most of the solvent is removed by rotary evaporation, and the remaining reaction solution is separated by column chromatography (the eluent is a liquid mixed with acetonitrile: water: saturated potassium nitrate = 80:4:1 by volume), and the orange part is collected. Most of the acetonitrile is removed by rotation, 1 g of sodium perchlorate is added, and stirred at room temperature for 1 h. The precipitate is collected by filtration. The crude product is dissolved in a small amount of acetonitrile and placed in a closed container containing ether solution. The ether slowly evaporates into the acetonitrile solution until a large amount of precipitation is precipitated. The precipitate is collected by filtration. The product is vacuum dried to obtain 118 mg of orange-red powder with a yield of 42%.
[0038] 1 H-NMR(δ / ppm,500MHz,DMSO-d6):9.12(d,J=8Hz,2H),8.87(dd,J=8Hz,4H),8.38 (d,J=8.5Hz,2H),8.28(d,J=8Hz,4H),8.23(t,J=15.5Hz,2H),8.12(t,J=15Hz,2H ),8.04(d,J=4Hz,2H),7.92(t,J=12Hz,2H),7.87(d,J=5Hz,2H),7.70(d,J=8.5H z, 4H), 7.62 (m, 4H), 7.55-7.48 (dq, 14H), 7.38-7.31 (dt, J = 21.5Hz, 6.56Hz, 6H).
[0039] Mass spectrometry (MALDI-TOF MS) calculated value: 1206.35 [M-2ClO4 - -H + ] + ; Experimental value: 1205.943[M-2ClO4 - -H + ] + .
[0040] Elemental analysis (%): C 75 H 51 Cl2N 11 Calculated for O8Ru.2H2O: C 62.46, H 3.84, N 10.68; Measured: C 62.49, H 3.75, N 10.61.
[0041] It can be seen that the structure of the prepared target complex is correct.
[0042] Example 3 Preparation of Carbazole-Modified Ruthenium (II) Complex Thin Film
[0043] The preparation route of the carbazole-modified ruthenium (II) complex thin film electrode is as follows:
[0044]
[0045] The synthesis method is:
[0046] 1. Cleaning of ITO glass electrode: Boil the ITO glass electrode with NH3·H2O:H2O2:H2O (V:V:V=1:1:5) at 70℃ for 40min, then clean it with deionized water ultrasonically, blow dry it with N2, soak it in a 5% by volume 3-aminopropyl-triethoxysilane ethanol solution for 12h, ultrasonically blow dry it with anhydrous ethanol, put it into a 1mmol / L diphenylamino-4-benzaldehyde solution, and add a drop of glacial acetic acid as a catalyst. Reflux for 24h under N2 protection, take it out and ultrasonically blow it with anhydrous ethanol solution, and blow dry it with N2.
[0047] 2. Preparation of carbazole-modified ruthenium (II) complex thin film electrode:
[0048] The ruthenium complex was dissolved in dichloromethane with 0.05M tetrabutylammonium hexafluorophosphate as the supporting electrolyte and the concentration of the ruthenium complex was 1mM. ITO was used as the working electrode, platinum electrode as the counter electrode, and Ag / AgNO3 electrode as the reference electrode. Nitrogen was introduced into the solution and ruthenium complex thin film electrode materials of different thicknesses were assembled using a constant potential method with a 40s time gradient.
[0049] Example 4 Study on the electrochemical properties of carbazole-modified ruthenium (II) complex thin film electrode
[0050] The electrochemical properties were studied on a CHI-660E electrochemical workstation, with the ruthenium complex film electrode material as the working electrode, the platinum electrode as the counter electrode, the Ag / AgNO3 electrode as the reference electrode, and a 0.1M tetrabutylammonium hexafluorohydrate CH2Cl2 solution as the supporting electrolyte. Because the film is a surface-controlled redox process, the Laviron theory was used to calculate the transfer factor α and the electron transfer rate constant k of the film. s . k s and α can be obtained by formulas (1) and (2):
[0051]
[0052]
[0053] Where n is the number of electrons transferred during the redox process, F is the Faraday constant, and v a and v care the intercepts on the X-axis after linear fitting of the oxidation peak data and the reduction peak data (see data and data processing results for details). Figure 2 ).
[0054] The relationship between the redox peak current and the scan rate of the thin film ruthenium (II) complex electropolymerized for 80s was measured. At low scan rates (scan rate range 0.05V~1.0V), see Figure 1 The oxidation peak current and reduction peak current of the film are proportional to the scan rate, indicating that the film is a surface-controlled redox process. Figure 2 At high scan rate (scan rate range 1.0V~10.0V), according to Laviron theory, the electron transfer rate constant of the film is calculated using formula (1) and formula (2) to be 6.26s -1 , the film has a large electron transfer rate constant, indicating that the film has high conductivity efficiency.
[0055] Example 5 Study on the photoelectrochemical properties of carbazole-modified ruthenium (II) complex thin film electrode
[0056] Take the ruthenium complex film that was electropolymerized at constant potential for 80s as an example:
[0057] 1. The photoelectrochemical properties were studied on a CHI-660E electrochemical workstation, with a 500W ultra-high-pressure spherical xenon lamp high-brightness light source system (Beijing Newbit Technology Co., Ltd.); the electrode area was 0.28 cm 2 The ruthenium complex thin film electrode material was used as the working electrode, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and the 0.1M Na2SO4 solution as the supporting electrolyte. The bias voltage was changed with a gradient of 0.1V, and the photocurrent-induction time (it) curve of the ruthenium complex thin film electrode under different bias voltages was measured.
[0058] The it curves of the obtained carbazole-modified ruthenium (II) complex film electrode at different bias voltages are shown in Figure 3 , where ah represents the bias voltage of -0.4V to +0.3V, and the bias voltage change interval is 0.1V. It can be seen that the more negative the applied bias voltage is, the stronger the photocurrent of the electropolymer film is. When the applied bias voltage is -0.4V, the photocurrent of the film is the largest. At 100mW / cm 2 Under white light irradiation, the film polymerized at constant potential for 80 s showed a maximum photocurrent density of 5.74 μA / cm in a 0.1 M Na2SO4 aqueous solution without air. 2 It is explained that the polarity of the photocurrent generated by the thin film electrode material is cathode photocurrent, and it has a high photocurrent generation efficiency and can be used as a photoelectric conversion device.
[0059] The prepared film was placed at room temperature for 3 months. When the bias voltage was -0.4 V, its photocurrent (curve b) was measured. Compared with the newly prepared film (curve a), its photocurrent was only attenuated by 11.7% (see Figure 4 ), indicating that the film has good stability and good adhesion on the electrode surface.
[0060] 2. The photoelectric conversion efficiency IPCE of the ruthenium (II) complex thin film electrode is calculated using formula 3:
[0061]
[0062] I is the photocurrent density, P inc is the intensity of incident light at a specific wavelength, and λ is the wavelength of the filter.
[0063] When the constant potential electropolymerization was performed for 80 s, the IPCE values of the carbazole-modified ruthenium (II) complex film electrode under monochromatic light of different wavelengths were shown in Figure 2. Figure 5 When the wavelength is 500nm, the photoelectric conversion efficiency is the highest, reaching 0.61%, indicating that the film has potential application value in photoelectric conversion devices.
[0064] 3. Effect of O2 on photocurrent of thin film electrodes
[0065] The bias voltage was -0.4 V, and the photocurrent of the carbazole-modified ruthenium (II) complex thin film electrode was measured under air balance, N2 flow, and O2 flow conditions.
[0066] Results Figure 6 At 100mW / cm 2 Under white light irradiation, the film subjected to constant potential electropolymerization for 80 s showed a maximum photocurrent density of 5.74 μA / cm in a 0.1 M Na2SO4 aqueous solution without air. 2 When oxygen is introduced into the electrolyte solution, the photocurrent density increases to 14.07 μA / cm 2 , indicating that the film material can be used as an oxygen sensor.
[0067] The above description is a detailed description of the preferred feasible embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modified changes completed under the technical spirit suggested by the present invention should fall within the patent scope covered by the present invention.
Claims
1. A carbazole-modified ruthenium complex, characterized in that: The structural formula of the carbazole-modified ruthenium complex is shown in formula (I): The chemical formula is [Ru(bpy)2HL](ClO4)2, where bpy represents bipyridine and HL is the ligand.
2. The carbazole-modified ruthenium complex according to claim 1, characterized in that The ligand is N-(4-(9H-carbazole-9-yl)phenyl)-4-(9H-carbazole-9-yl)-N-(4-(3a,11b-dihydro-1H-imidazo[4,5-f][1,10]phenanthroline-2-yl)phenyl)aniline, and the structural formula is shown in formula (II):
3. The method for preparing the carbazole-modified ruthenium complex according to claim 1, characterized in that: The following steps are involved: (1) Synthesis of ligand HL: 1,10-phenanthroline-5,6-dione, 4-(bis(4-(9H-carbazole-9-yl)phenyl)amino)benzaldehyde, ammonium acetate and glacial acetic acid are placed in a reaction vessel and reacted at 120±1°C. After the reaction is completed, the reaction solution is quickly poured into ice water, and the pH of the solution is adjusted to neutral with ammonia water. The solution is allowed to stand and filtered to obtain a crude product. The crude product is recrystallized with a mixed solvent of DMF / water, filtered, the precipitate is collected, and the filter cake is washed with anhydrous ethanol. The product is vacuum dried to obtain a yellow-brown powdery solid, which is the ligand HL. (2) Synthesis of the complex [Ru(bpy)2HL](ClO4)2: The ligand HL and Ru(bpy)2Cl2 were dispersed in anhydrous ethanol and refluxed in the dark under nitrogen protection. After cooling, most of the solvent was removed by rotary evaporation. The remaining reaction solution was separated by column chromatography and the main orange portion was collected. After most of the acetonitrile was removed by rotary evaporation, sodium perchlorate solution was added thereto. After stirring, the precipitate was collected by filtration. The precipitate was dissolved with a small amount of acetonitrile, and recrystallized by diffusion with ether / acetonitrile. After vacuum drying, an orange-red powder was obtained.
4. The preparation method according to claim 3, characterized in that: In step (1), the molar ratio of 1,10-phenanthroline-5,6-dione, 4-(bis(4-(9H-carbazole-9-yl)phenyl)amino)benzaldehyde and ammonium acetate is 1:1:
20.
5. The preparation method according to claim 3, characterized in that: In step (2), the molar ratio of the ligand HL to Ru(bpy)2Cl2 is 1:
1.
6. The preparation method according to claim 3, characterized in that: In step (1), the reaction time is 2 h.
7. Electropolymerized thin films based on ruthenium complexes, characterized in that: The electropolymerized film is obtained by modifying the ruthenium complex described in claim 1 onto an ITO electrode using a constant potential electropolymerization method.
8. The method for preparing an electropolymerized thin film based on a ruthenium complex according to claim 7, characterized in that: The following steps are involved: First, the ITO glass electrode was cleaned, and then the ruthenium complex was dissolved in dichloromethane. Tetrabutylammonium hexafluorophosphate was used as the supporting electrolyte, ITO was used as the working electrode, the platinum electrode was used as the counter electrode, and the Ag / AgNO3 electrode was used as the reference electrode. Nitrogen was introduced into the solution, and the constant potential method was used with a time gradient of 40 s to assemble ruthenium complex electropolymerized films of different thicknesses.
9. The method for preparing an electropolymerized film according to claim 8, characterized in that: The concentration of the ruthenium complex in dichloromethane was 1 mM.
10. The use of the electropolymerized film according to claim 7, characterized in that: Refers to the application of electropolymer films in energy conversion and oxygen sensors.